COMPARATIVE STUDY BETWEEN CONTENT BASED AND TASK BASED INSTRUCTION IN TEACHING SPEAKING SKILL A CASE STUDY AT THE SECOND YEAR STUDENTS OF MADRASAH TSANAWIYAH DARUL ISHLAH IRENG LAUQ - Suparlan Suparlan; Mul Muliadi (LPPM Institut Pendidikan Nusantara Global, 2020)
This study propose to find out the different effect between Content Based Instruction and Task Based Instruction in teaching speaking skill. The population of the study is the second year students of Madrasah Tsanawiyah Darul Ishlah Ireng Lauq with totaling students 222 and consisting of 6 classes. 74 students are taken as the samples which are divided into two groups; i.e. “X” group and “Y” group consisting of 37 students for each group. To get the whole data needed, test instruments in the forms of post-test was employed. Having deeply analyzed the whole data it is found that the student’s ability using Content Based Instruction method is higher than the students using Task Based Instruction method. This fact can also be seen from the mean score of “X” group which reaches 77, 18 and the means core of “Y” group which reaches 74, 59. This can also simply mean that the use of Content Based Instruction method and Task Based Instruction have different effect in teaching speaking skill in the second year students of Madrasah Tsanawiyah Darul Ishlah Ireng Lauq. Furthermore, Based on the statistical computation, interval confidence of 90%, 80% (0, 10 and 0, 20) t-test= 0,804 is lower than t-table=1,688 and 1,306. Which is automatically means that the both of them are not suitable for teaching spiking skill.